Music therapy for the treatment of anxiety: a systematic review with multilevel meta-analysesResearch in context - Martina de Witte; Sonja Aalbers; Annemieke Vink; Stijn Friederichs; Anne Knapen; Thomas Pelgrim; Amit Lampit; Felicity A. Baker; Susan van Hooren (EClinicalMedicine)
Summary: Background: A considerable number of published clinical trials have examined the anxiety-reducing effects of music therapy interventions across several settings, including mental health care, medical environments, and work- and study-related contexts. Music therapy involves personally tailored music interventions that are designed and implemented by qualified music therapists to meet the specific health needs of individual patients. Methods: To summarise this evidence base, we conducted a linear restricted maximum likelihood multilevel meta-analysis searching multiple electronic databases (CINAHL, Cochran Central Register of Controlled Trials, PubMed, Embase, PsycInfo, Web of Science core collection), from inception to 12th February 2025. The primary measure was the effects of music therapy on 7 psychological anxiety outcomes and physiological outcomes. The secondary measures were outcome, study, sample, or intervention design factors that moderate the effects of music therapy interventions. Meta-analyses were performed on 93 effect sizes (ES) from 51 studies to assess the magnitude of effects of music therapy targeting anxiety outcomes, and to compare effects across key intervention and study design factors. PROSPERO registration (CRD42024495801). Findings: Of the 10,210 identified records, 6147 records were screened and 51 articles meeting the research criteria were included. Results showed an overall medium effect of music therapy across all anxiety outcomes (g = 0.357, [0.201, 0.514]; 51 trials, 93 ES), of which a medium effect was found in participants’ self-reported anxiety (g = 0.410, [0.236, 0.585]; 50 trials, 61 ES) and a small non-significant effect in physiological outcomes (g = 0.153 [−0.153, 0.400]; 13 trials, 32 ES). Subgroup analyses showed significant larger effects for receptive and combination of active and receptive interventions when compared with active interventions. Interpretation: The findings suggest that music therapy, particularly receptive methods or combinations of receptive and active approaches, offer effective, flexible, and scalable interventions for reducing anxiety symptoms, offering psychological benefits that enhance patient autonomy and quality of life, though its impact on physiological outcomes and long-term effects requires further research. Funding: This work was supported by a McKenzie Postdoctoral Fellowship from the University of Melbourne (MdW), and NHL Stenden University of Applied Sciences through internal postdoctoral research funding (SA).